Refugee Health Elective - Helenka Stone; Ray Choi; Eva Aagaard; Paritosh Kaul; Jennifer Gong; Daniel Savin; Barbara Hummel; Brandie Andrews; Jamaluddin Moloo; Anastasia Petkova (Association of American Medical Colleges, 2013)
Abstract World disasters, conflicts, and persecutions have resulted in growing refugee populations worldwide. Future medical professionals will need to be trained to provide culturally effective care to this population. This curriculum is designed to introduce medical and other health professions students to the common medical, dental, and psychosocial issues faced by refugees in the United States. Each of the eight topics is presented in a 1-hour session, in either a lecture or a panel presentation format. The lectures include an introductory session on refugee health and resettlement programs in the US as well as lectures on the medical care of refugees, common oral health problems of refugees, refugee mental health, and challenges and ethical dilemmas of providing culturally effective care. Panels cover life as a refugee, their experience with resettlement in the US, and their experience with the health care system. At the University of Colorado School of Medicine, this elective was originally offered to first and second-year medical students. However, all health professions students would benefit in some way from the topics presented. Speakers were recruited from local clinics, resettlement agencies, and refugee populations to give presentations and discuss the various topics. Each had a presentation or case from their personal experience with refugees; the panelists discussed their work and obstacles to providing optimal resettlement or medical care to refugees. The refugees themselves described their own backgrounds to the extent they felt comfortable with, and relayed their experiences with health care in the United States. From the qualitative data gleaned via individual sessions and overall course evaluations, students were eager to get involved in refugee clinics and resettlement agencies. The next step will involve creating a service-learning experience that will benefit the refugee population and further prepare health professions students to provide culturally effective care.